Assessment of gubernacular canal frequency with CBCT in a group of Turkish population - Mehmet Emin Dogan; Nurbanu Uluısık; Mehmet Sinan Dogan (BMC, 2023)
Abstract Objective The aim of this study is to investigate the frequency of the gubernacular canal observed on cone-beam computed tomography (CBCT) images in a group of Turkish populations according to age and gender. Materials and methods CBCT images of 500 cases were evaluated retrospectively, and a total of 117 impacted or erupting teeth were included in the study, and the presence of gubernacular canal was recorded according to age, gender and eruption status of the tooth. SPSS program was used for statistical analysis. Results The mean age of 117 buried/continuing patients was 17 ± 15.32, 55 (47%) were female and were 62 (53%) male patients. Presence of gubernacular canal was observed in 91 (77.8%) cases and this duct was not detected in 26 (22.2%) cases. While 40.2% of female were found to have canals, 37.6% of male had canals. When the presence of canals was examined, the presence of canals was found to be significantly higher in the erupting teeth. A significant difference was found when analyzed according to the mean age. Conclusions CBCT is a useful method of detecting the gubernacular canal. The presence of gubernacular canal was significantly higher in erupting teeth.